The Effect of Game Addiction on Student's Academic Procrastination - Jannah, Nurul; Ade Ariani , Winda; Kartika Sari , Widya; Titin Sumarni , Ade; Nur Aisha , Angelica (Corolla International Conference, 2025)
This study seeks to examine the levels of game addiction and academic procrastination among students, as well as to analyze the effect of game addiction on academic procrastination at State Senior High School 1 Central Bengkulu. The rationale for this research is based on the growing prevalence of online gaming among adolescents, which has been associated with changes in learning behavior and increased tendency to postpone academic responsibilities. The study employed a quantitative methodology with a descriptive design and utilized multiple linear regression analysis. The population comprised all students of State Senior High School 1 Central Bengkulu, from which a sample og 165 students was selected through stratified random sampling. Data were collected using questionnaires developed to assess students’ levels of game addiction and academic procrastination. The findings indicated that the level og fame addiction among students was classified as high with 84 studentd as moderately high, involving 95 students. Statistical analysis conducted using the Statistical Prouduct and Service Solution (SPSS) software revealed a significance value (sig) of 0.00 which is lower that the threshold of 0.05 leading to the rejection of the null hypothesis (HO). This result demonstrates that game addiction has a significant influence on academic procrastination among students. Overall, the results suggest that higher levels of game addiction are associated with a greater tendency for students to engage in academic procrastination. It is expected that the findings of this study can be used as a reference for teachers, school counselors, and perents in providing appropriate guidance and supervision to reduce the negative effects of gaming behavior on students’ academic performance and learning discipline.